Hubungan parameter fisika-kimia perairan dengan kelimpahan plankton di Samudera Hindia bagian Barat Daya - Rani Novia; Adnan .; Irwan Ramadhan Ritonga (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2016)
Abstract. The aims of this research was to examine the water quality parameters and plankton abundance and its relationships in the Southwestern of Indian Ocean. This is a quantitative descriptive research. Planktons were sampled using plankton net, and water samples were taken using Conductivity, Temperature, Depth (CTD) where the water samples colleted in the Nansen Bottle No. 1 (surface water) at seven sampling stations. The results showed that there were 25 species of planktons belonging into seven classes, i.e., Bacillariophyceae, Ciliate, Crustacea, Cyanobacteria, Dinophyceae, Flagellata, and Maxillopoda. The highest value of abundance of plankton was found at station 6 with 7255 ind. L-1, the value of diversity index of plankton was at moderate category, and there was no predominant species was occurred in the community. Bivariate correlation analysis results of Person's showed that the temperature and Dissolved Oxygen (DO) were positively correlated to the plankton abudance, while pH, conductivity, TDS, salinity were negatively correlated with abundances of plankton.Keywords: Abundance of plankton, linkages, water quality, Indian Ocean of Southwestern Abstrak. Penelitian ini bertujuan untuk mengetahui jenis dan kelimpahan plankton dan kualitas air serta hubungan antara kelimpahan plankton dengan parameter fisika-kimia perairan di Samudera Hindia bagian Barat Daya. Penelitian ini merupakan penelitian deskriptif kuantitatif, pengambilan sampel plankton menggunakan plankton net, dan sampel air menggunakan CTD (Conductivity, Temperature Depth) dimana sampel air yang diambil pada botol nansen No. 1 (sampel air permukaan) pada 7 titik stasiun. Hasil penelitian ditemukan 25 spesies plankton yang termasuk ke dalam 7 kelas, yaitu Bacillariophyceae, Ciliata, Crustacea, Cyanobacteria, Dinophyceae, Flagellata, dan Maxillopoda. Kelimpahan plankton tertinggi terdapat pada stasiun 6 dengan 7255 ind/L, indeks keragaman plankton pada kondisi sedang, dan tidak terjadi dominasi spesies dalam komunitas. Hasil analisis korelasi Bivariate Person’s menunjukkan suhu dan DO (Dissolved Oxygen) berkorelasi positif terhadap kelimpahan plankton, sedangkan pH, konduktifitas, TDS, salinitas berkorelasi negative dengan kelimpahan plankton. Kata kunci: Kelimpahan Plankton, Keterkaitan, Kualitas air, Samudera Hindia bagian Barat Daya